Innovation and entrepreneurship - Bessant, John; Tidd, Joe (United Kingdom : John Wiley & Son, Inc., 2011)
This book has been developed specifically for undergraduate students of business and management studies, and science and engineering students studying courses on these subjects.
Entrepreneurial goals and context -- Recognising the opportunity -- Finding the resources -- Developing the venture -- Creating value
Includes index.
Keywords: INNOVATION